Electromechanics complex of the wind power generating fluidizer the use in underground making of iron-ore mines - Сінчук, Олег Миколайович; Бойко, Сергій Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
Today, the problem of high-quality power supply to consumers occupies one of the most prominent places in power engineering and electrical engineering. Considering the wind electromechanical complex operation, it is necessary to pay attention to the fact that the wind wheel operation is variable in nature, caused by the stochastic feature of the air flow. Operation of generator, which is a part of the wind electromechanical complex, depends directly on the wind wheel operation nature, therefore, the generator output parameters such as voltage and frequency will vary depending on the air flow speed and, consequently, generator shaft rotation speed. In view of the above features, the issue of output parameters control of wind electromechanical complex is relevant and so there is a need to solve this problem. It is proposed to solve the problem of variable output generator parameters by creating a control system based on microcontroller. Control is proposed to carry out using fuzzy sets, which will allow to take into account changes in the system, caused by the stochastic nature of air flows. Using this control system for wind electromechanical complexes will provide stable and high-quality power supply to consumers.